2021
DOI: 10.1007/s10800-021-01585-7
|View full text |Cite
|
Sign up to set email alerts
|

Polymer-metal complexes as emerging catalysts for electrochemical reduction of carbon dioxide

Abstract: A class of metal-doped polyanilines (PANIs) was synthesized and investigated as electrocatalysts for the carbon dioxide reduction reaction (CO2RR). These materials show good affinity for the electrode substrate and allow to obtain stable binder-free electrodes, avoiding the utilization of expensive ionomer and additives. The emeraldine-base polyaniline (EB-PANI), in absence of metal dopant, shows negligible electrocatalytic activity and selectivity toward the CO2RR. Such behavior significantly improves once EB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…Single-atom catalysts (SACs), possessing superior catalytic activity and maximum atom utilization, have been widely considered as efficient catalysts. Especially, metal-coordinated four N-doped carbon two-dimensional SACs (M–N 4 –C, M = Fe, Co, Ni, Cu, etc.) have proven to be promising CO 2 RR electrocatalysts. ,, Furthermore, the coordination environment and bonding characteristics of SACs play important roles in the regulation and optimization of catalytic performance, where heteroatomic doping is an effective strategy. , Compared with the introduction of impurity atoms in the carbon material plane, recent studies have reported that the introduction of an additional highly electronegative oxygen atom in the M–N 4 –C (M = Fe and Ni) axis can achieve efficient electrocatalytic CO 2 RR. Wang et al revealed that CO 2 RR on an Fe–N 4 O-doped carbon material achieved a high Faradaic efficiency (FE) of CO of 96% with a low overpotential of 0.47 V. In addition, a Ni–N 4 –O/C catalytic site, by constructing a Ni site coordinated with four N atoms and one axial O atom, exhibited a FE CO of approximately 99.2% at −0.9 V . Chen et al reported an Fe 1 N 4 –O 1 electrocatalyst with an axial O atom coordinated at the Fe site by chelating an Fe precursor with an O-doped carbonaceous support, which showed outstanding catalytic performance of nearly 100% FE CO over a wide potential range.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Single-atom catalysts (SACs), possessing superior catalytic activity and maximum atom utilization, have been widely considered as efficient catalysts. Especially, metal-coordinated four N-doped carbon two-dimensional SACs (M–N 4 –C, M = Fe, Co, Ni, Cu, etc.) have proven to be promising CO 2 RR electrocatalysts. ,, Furthermore, the coordination environment and bonding characteristics of SACs play important roles in the regulation and optimization of catalytic performance, where heteroatomic doping is an effective strategy. , Compared with the introduction of impurity atoms in the carbon material plane, recent studies have reported that the introduction of an additional highly electronegative oxygen atom in the M–N 4 –C (M = Fe and Ni) axis can achieve efficient electrocatalytic CO 2 RR. Wang et al revealed that CO 2 RR on an Fe–N 4 O-doped carbon material achieved a high Faradaic efficiency (FE) of CO of 96% with a low overpotential of 0.47 V. In addition, a Ni–N 4 –O/C catalytic site, by constructing a Ni site coordinated with four N atoms and one axial O atom, exhibited a FE CO of approximately 99.2% at −0.9 V . Chen et al reported an Fe 1 N 4 –O 1 electrocatalyst with an axial O atom coordinated at the Fe site by chelating an Fe precursor with an O-doped carbonaceous support, which showed outstanding catalytic performance of nearly 100% FE CO over a wide potential range.…”
Section: Introductionmentioning
confidence: 99%
“…have proven to be promising CO 2 RR electrocatalysts. [21][22][23][24][25][26][27]81,82 Furthermore, the coordination environment and bonding characteristics of SACs play important roles in the regulation and optimization of catalytic performance, where heteroatomic doping is an effective strategy. 28,29 Compared with the introduction of impurity atoms in the carbon material plane, recent studies have reported that the introduction of an additional highly electronegative oxygen atom in the M−N 4 −C (M = Fe and Ni) axis can achieve efficient electrocatalytic CO 2 RR.…”
Section: ■ Introductionmentioning
confidence: 99%
“…crystallography.net/cod/index.php). Since there are no contributions from the EB-PANI, 9 XRD data suggest that the SnO 2 /PANI catalyst consists of an amorphous polymeric matrix, decorated with nanometric SnO 2 -like structures (∼1.5 nm in size, based on Pawley refinement). Both morphology and structure were finally investigated with transmission electron microscopy (TEM).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Electrochemical Characterization. Due to the chemical nature as an ionomer of the polyaniline, 9 the catalyst was drop casted onto a gas diffusion electrode without the presence of a binder for the fabrication of the cathode electrode. The catalyst ink was composed of catalyst powder mixed with Vulcan carbon nanoparticles with a weight ratio of 9:1 for a total powder density of 1 mg cm −2 on each electrode; the introduction of carbon nanoparticles in the slurry was intended to increase the overall electrical conductivity across the electrode.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation